Incidence of Fumonisin B-2 Production by Aspergillus niger in Portuguese Wine Regions - Abrunhosa, Luís (2011)
Fumonisin B2 (FB2) was recently found to be produced by Aspergillus niger. When grape-derived products were subsequently analyzed, FB2 contamination was found in raisins, must, and wine. This study evaluated 681 strains of black aspergilli species isolated from Portuguese wine grapes for FB2 production when grown on Czapek yeast agar. FB2 was not detected in Aspergillus carbonarius (n = 75) or Aspergillus ibericus (n = 9) strains, but it was detected in 176 (29%) of the strains belonging to A. niger aggregate (n = 597). The amount of FB2 produced by these strains ranged from 0.003 to 6.0 mg/kg with a mean of 0.66 mg/kg. The Alentejo region had the lowest percentage (10%) of fumonisinogenic strains, whereas the Douro region had the highest percentage of fumonisinogenic strains (38%). Only 10 strains were found to produce FB2 and ochratoxin A simultaneously.